Power Quality Improvement Wind Energy System Using Cascaded Multilevel Inverter - Sathiyanarayanan, J.S.; Kumar, A. S. (International Journal of Renewable Energy Development, 2013)
In this paper, a wind energy conversion system based on a cascaded H-bridgemultilevel inverter (CHBMLI) topology has been proposed to be used for the grid interface of largesplit winding alternators (SWAs). A new method has been suggested for the generation of referencecurrents for the voltage source inverter (VSI) depending upon the available wind power. TheCHBMLI has been used as a VSI and operated in a current control mode order to achieve theobjectives of real power injection and load compensation (power factor correction, load balancing,and harmonic compensation) based on the proposed reference generation scheme. In the fieldexcitation control of SWA provides a single means vary the dc link voltages of all the CHBssimultaneously and proportionately.